Avaliação do ciclo de vida (ACV) do etanol combustível com elevados teores de água - Peyrot, Caroline (2018)
The small-scale production of fuel ethanol has serious process-related energy efficiency problems. However, increasing the hydration content of fuel ethanol proposes an alternative to improve the energy balance of the production process, and also reduce GHG emissions in the burning of biofuel without compromising the operating system in thermal machines. A Life Cycle Assessment (LCA) and Energy Efficiency Analysis (EEA) were performed to compare and evaluate the stages of industrial production and stationary end use for fuel ethanol with hydration levels of 5%, 10%, 20% and 30% in volumetric composition. The environmental performance indicated a design of environmental impact minimization of over 25% in the categories respiratory organics (-27%), climate change (-41%), radiation (- 26%) and land use (-110%) Eco-indicator 99. NER (Net Energy Ratio) and NEB (Net Energy Balance) efficiency metrics showed a surplus of 1.3 and a balance of 424.26 GJ, respectively, for the ethanol production scenario with 30% of hydration and the use of bagasse (co-product) in thermal energy cogeneration. The raw material and the electric energy, in this order, were the flows responsible for the reduction of environmental impact and better energy efficiency with the increase of the hydration of the fuel ethanol. The comparison of fuels in the two evaluations carried out indicated that the best scenario for small-scale production and fixed- source final use for electric power generation was observed for 70% v / v ethanol fuel and the use of the bagasse in thermal energy cogeneration.